Meningitis caused by an alkali-producing pseudomonad. - Cowlishaw, W A (1976)
The clinical and microbiological features of a case of meningitis, due to an alkali-producing pseudomonad which closely resembles Pseudomonas pseudoalcaligenes, are described. A respiratory infection and a course of antibiotic therapy before admission to hospital may have been predisposing factors to opportunistic infection by this normally saprophytic organism. The problems of identifying alkali-producing pseudomonads are discussed.